Prevalence of use of performance-enhancing substances among United States adolescents - Castillo, E. M.; Comstock, R. D. (Pediatric Clinics of North America, 2007)
Adolescents may regard the use of performance-enhancing substances as an easy means to gain self-esteem through improved body appearance and athletic performance. The use of performance-enhancing substances by adolescents is particularly troubling because safety data are largely lacking. This poses a dilemma for the pediatrician who needs correct information, including the potential efficacy and negative health effects of such substances, to identify the patients in need of counseling and to find the best way to help adolescent patients make informed decisions to promote healthy behaviors. This article is intended to assist pediatricians by providing a summary of the current state of knowledge regarding the prevalence of use of performance-enhancing substances by United States adolescents.